Smart Finance, Stronger Business: Digital Financial Management Impact on MSME Sustainability - Yulianti, Yulianti; Burham Isnanto; Amri , Amri; Iput Yolantika (PT. ALHAFI BERKAH INDONESIA, 2025)
The effect of digital financial management on the long-term viability of SMEs in Pangkalpinang City is examined in this study. This study looks at how business financial management and the sustainability of SMEs are affected by the use of digital financial technology, digital financial literacy, digital security awareness, and digital payment integration. Using a quantitative approach and survey methodology, the study aims to survey 389 MSME owners and managers in Pangkalpinang who were chosen by simple random sampling. Structural Equation Modeling-Partial Least Square (SEM-PLS) was used to analyze the data. The findings of the study indicate that the Adoption of Digital Financial Technology has the strongest influence on Business Financial Management (0.716) and MSME Sustainability (0.934), followed by Digital Financial Literacy which significantly affects Business Financial Management (0.603) and MSME Sustainability (0.735). Digital Security Awareness and Digital Payment Integration also show a positive influence on both variables. Business Financial Management has a positive effect on the Sustainability of SMEs (0.605), with an R Square value of 0.742 indicating that the research model has strong predictive capability. These findings imply the importance of digital transformation in supporting the sustainability of MSMEs through the enhancement of operational efficiency and the optimisation of financial resource management.